2005
DOI: 10.1099/jmm.0.45932-0
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic and phenotypic modifications of Yersinia pestis under calcium and glucose concentrations simulating the mammalian bloodstream environment

Abstract: To study the possible mechanism of extracellular resistance to phagocytes developed by Yersinia pestis in the early stage of plague infection, the behaviour of two Y. pestis strains, the vaccine EV-76 and fully virulent 231 (LD 50 , 10 c.f.u.), was studied in-depth after cultivation in vitro at the host temperature in conditions simulating the bloodstream environment of mammals. For this, two standard basal media supplemented with calcium and glucose in appropriate concentrations were employed: Hottinger broth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…In addition, Y. pestis EV ⌬lpxM showed a lower growth rate in vitro but replicated and remained at the site of inoculation significantly longer than the parental EV NIIEG strain (39). Therefore, the better immunogenicity of Y. pestis EV ⌬lpxM was most likely due to these pleiotropic effects, including the dampening of the host innate immune response as well as enhanced bacterial persistence, leading to the activation of adaptive immunity (39,63).…”
Section: Discussionmentioning
confidence: 96%
“…In addition, Y. pestis EV ⌬lpxM showed a lower growth rate in vitro but replicated and remained at the site of inoculation significantly longer than the parental EV NIIEG strain (39). Therefore, the better immunogenicity of Y. pestis EV ⌬lpxM was most likely due to these pleiotropic effects, including the dampening of the host innate immune response as well as enhanced bacterial persistence, leading to the activation of adaptive immunity (39,63).…”
Section: Discussionmentioning
confidence: 96%
“…To identify the ability of the cells of Y. pestis EV NIIEG and its Δ lpxM derivative to form a capsule-like substance, the bacteria were analysed by electron microscopy as described elsewhere [39]. For this purpose, bacterial samples were examined with a JEOL model JSM-U3 microscope.…”
Section: Methodsmentioning
confidence: 99%
“…For this purpose, bacterial samples were examined with a JEOL model JSM-U3 microscope. Test samples of bacterial suspensions were placed on carbon-coated collodion grids followed by the treatment and negative staining as described [39]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously it was suggested that the bloodstream environment induces bacterial resistance to phagocytosis by suppression of Y. pestis-specific antigens (42). We hypothesized that glucose may induce phenomena previously unrecognized in Y. pestis, such as the observed changes in lipid and protein compositions and/or the induction of the MV secretion system.…”
Section: (C) Two (As-c-12 and Mf-73) Y Pestis Kim6mentioning
confidence: 99%